Meningkatkan Efisiensi Pengembangan Perangkat Lunak Melalui Transparansi dan Kolaborasi dengan Ubuntu - Rakhmadi Rahman; Syifa Tri Agusriani; Rina Rina (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Efficiency in software development is crucial to meet the increasing demands of the market today. This efficiency encompasses not only faster production times but also maintaining high quality and user satisfaction. Transparency and collaboration have been identified as critical factors in achieving this efficiency. Ubuntu, with its open-source nature, offers various features that effectively support these principles. Software development is a pivotal process in the current technological era, where innovation and development speed are keys to success. Ubuntu, as one of the popular Linux distributions based on open source, has played a significant role in facilitating this process through its transparent and collaborative approach. This article aims to explore how Ubuntu enhances software development efficiency through the principles of transparency and collaboration it upholds.This article will delve deeper into how transparency and collaboration within the Ubuntu ecosystem can significantly contribute to improving software development efficiency. By focusing on these principles, Ubuntu continues to be a top choice in the modern software development world, bringing benefits to developers, companies, and end-users worldwide.